Density Functional study on the transesterification of triacetin assisted by cooperative weak interactions via a gold heterogeneous catalyst: Insights into biodiesel production mechanisms. (15th August 2017) - Delesma, Cornelio; Castillo, Roger; Sevilla-Camacho, P.Y.; Sebastian, P.J.; Muñiz, Jesús
Graphical abstract: Highlights: A DFT study reveals the feasibility to obtain biodiesel via a gold catalyst. Triacetin is used a model of triglycerides to reduce computational time. The triacetin transesterification is achieved by a van der Waals-driven attraction. Despite its nobility, Au is capable of catalyzing reactions that produce biofuels. Abstract: A Density Functional study predicting a heterogeneous-catalyzed reaction to obtain biodiesel was performed. Triacetin simulated triglycerides in the presence of an Au(1 1 1) surface as the heterogeneous catalyst. Methoxy was implemented as alcohol solvent to understand the reaction trajectory along a three-step transesterification process. Reactants and products in the three-step process are adsorbed on the Au substrate through non-covalent interactions of the electrostatic-type, which are also mediated by a van der Waals attraction. Density of states indicated that the electronic structure nature of Au is preserved after the interaction with the organic moieties. This may be addressed to an enhanced stability of the Au(1 1 1) catalyst through the overall reaction. Charge transfer analysis revealed that the Au surface oxidation aids in the transesterification of triacetin and evidences that gold plays an important role in this catalytic process. Such results may provide fundamental insights into the design of heterogeneous catalysts for biodiesel production.